Political Islam - "Hroub, Khaled. (ed.)" (London, 2010)
This volume offers a comprehensive discussion of the contemporary debates within political Islam, providing an in-depth analysis of the specific movements, countries and regions in the Arab world and Israel. The contributors contend that the evolution of Islamic movements is contextual rather than ideological. Therefore, Islamic movements are best understood individually within their own historical, socio-political and cultural setting. Political Islam is an essential reference for academics, researchers and the media, as well as general readers with an interest in Islamic political debates. Contributors include Abdullah Baabood, Youcef Bouandel, Abdelwahab El-Affendi, Kamal Helbawy, Roel Meijer, Ibrahim Moussawi, Tariq Ramadan, Tilde Rosmer, Murad Batal al-Shishani, Sara Silvestri and Camille Tawil.
Keywords: Islam and politics